1997
DOI: 10.1038/ki.1997.444
|View full text |Cite
|
Sign up to set email alerts
|

Expression of polycystin in mouse metanephros and extra-metanephric tissues

Abstract: The presence of messenger RNA for the mouse homologue of the polycystic kidney disease 1 gene (PKD1) was demonstrated by reverse transcription-polymerase chain reaction (RT-PCR) methods in mouse embryo messenger RNA. A single locus for the PKD1 gene was detected on mouse chromosome 17 by fluorescent in situ hybridization. Immunoprecipitation of proteins from [35S] methionine-labeled mouse metanephric explants with an anti-polycystin antibody (Pc1) revealed high molecular weight bands, the highest being > 400 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 21 publications
5
18
0
Order By: Relevance
“…In the kidney, Pkd1 expression was found to be highly developmentally regulated, with earliest expression in uninduced mesenchyme followed by the induced epithelium and with persistence of expression in the mature glomeruli, collecting tubules, and pelvis. These findings are supported by human and murine immunolocalization studies that demonstrate PKD1 protein in condensing mesenchyme (Van Adelsberg et al, 1997) and induced epithelium of the developing nephron (Palson et al, 1996;Ward et al, 1996;Geng et al, 1997;Griffin et al, 1997;Ibraghimov-Beskrovnaya et al, 1997;Van Adelsberg et al, 1997). The temporal expression of Pkd1 in the kidney is consistent with its role as a renal developmental switch that is turned on in epithelial induction and growth, and persists at detectable expression levels in the maturation and maintenance of the normal renal tubule.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In the kidney, Pkd1 expression was found to be highly developmentally regulated, with earliest expression in uninduced mesenchyme followed by the induced epithelium and with persistence of expression in the mature glomeruli, collecting tubules, and pelvis. These findings are supported by human and murine immunolocalization studies that demonstrate PKD1 protein in condensing mesenchyme (Van Adelsberg et al, 1997) and induced epithelium of the developing nephron (Palson et al, 1996;Ward et al, 1996;Geng et al, 1997;Griffin et al, 1997;Ibraghimov-Beskrovnaya et al, 1997;Van Adelsberg et al, 1997). The temporal expression of Pkd1 in the kidney is consistent with its role as a renal developmental switch that is turned on in epithelial induction and growth, and persists at detectable expression levels in the maturation and maintenance of the normal renal tubule.…”
Section: Discussionsupporting
confidence: 74%
“…In agreement with the above model of membraneassociated protein, immunohistochemical studies have localized polycystin-1 to the plasma membrane in renal epithelial cells of fetal and adult tissue (Palson et al, 1996;Ward et al, 1996;Geng et al, 1997;Griffin et al, 1997;Ibraghimov-Beskrovnaya et al, 1997;Van Adelsberg et al, 1997). In ADPKD, however, the polycystin-1 appears to be overexpressed in the renal epithelium of most (but not all) cysts.…”
Section: Introductionsupporting
confidence: 56%
“…These domains mediate protein-protein and protein-carbohydrate interactions in other proteins, and by analogy, are likely to mediate similar interactions in polycystin-1. We and others have shown that polycystin-1 is expressed in the plasma membrane of epithelial cells (12)(13)(14)(15)(16)(17). This observation is consistent with the hypothesis that polycystin-1 might interact with an extracellular ligand or ligands.…”
Section: Introductionsupporting
confidence: 77%
“…Previous data based on immunohistochemistry and in vitro organ culture systems have suggested a role for polycystin-1 in ureteric bud growth and branching during kidney development (23,39,40). This article, however, demonstrates that polycystin-1 does not play a major role in early nephrogenesis.…”
Section: Discussionmentioning
confidence: 45%